Furthering judicial education : proceedings of the conference of judicial schools in Latin America - Larios Ochaita, Carlos; Malik, Waleed Haider, 1957-; World Bank.; Guatemala. Corte Suprema de Justicia (Washington, D.C. : World Bank, 2002)
'Furthering Judicial Education' is a collection of papers presented at the international conference on judicial excellence in Guatemala in October 2001. This report contains the proceedings of the conference which focused on the various facets of judicial education and its challenges and opportunities. The aim of this report is to assist judiciaries improve the performance of judicial education programs and systems.
Papers presented at the international conference on judicial excellence in Guatemala on October 8, 2001 entitled "Toward judicial excellence" organized by the Supreme Court of Justice of Guatemala and the World Bank.
Includes bibliographical references (p. 84-85).
oif 02/03/15
Loan
Keywords: Judges -- Education -- Latin America -- Congresses